Model dynamics and control of the searching and tracking head placed on a moving object - Krzysztofik, I.; Koruba, Z. (Видавництво Львівської політехніки, 2011)
The paper presents the concept of searching, location and tracking of low-flying air targets through the head placed on a moving object, such as a self-propelled anti-aircraft missile system or a ship. Moreover, equations of motion of this type control head are derived.
Keywords: dynamics and control; searching and tracking head; missile launcher